Impact of Leadership and Gender on Civil Servants’ Resilience in the Romanian State’s Public Administration - Alina G. Profiroiu; Corina C. Nastacă (Transylvanian Review of Administrative Sciences, 2022)
The research analyses the leadership styles practiced in the Romanian public administration, the gender differences regarding the practiced leadership and in terms of exhibiting behaviors that could lead to the development of civil servants’ resilience, trying to investigate the relation between leadership, gender, and resilience. The paper contributes to the scientific literature in the field by analyzing three concepts that are not usually explored together and especially in the public administration. The research methodology consists of a sociological survey conducted in the Romanian public administration where 766 civil servants agreed to participate. The research revealed that the studied leaders present a mix of characteristics where transformational and transactional behaviors are predominant. Regarding gender differences, both men and women are considered to lead in a similar manner, but a higher preference for male leaders was observed. Men’s leadership behaviors are better appreciated, indicating the presence of gender stereotypes and a certain level of prejudice against women. The studied leaders possess the necessary characteristics for developing civil servants’ resilience, being perceived as exhibiting supportive, encouraging, and motivating attitudes when their subordinates faced difficult moments in their careers. Also, the existence of a direct relation between transformational leadership and resilience was observed.